DAILY LIVING SKILLS PADA ANAK DENGAN GANGGUAN AUTISME - Sari, Pustika (Universitas Ahmad Dahlan, 2014)
ABSTRACTThis study aimed to determine the ability of daily living skills in children wit autism. Research method used was qualitative.Subjects in this study were three children who had been diagnosed with autism over the age of 6 years. Data collection techniques in this study was conducted using semi-structured interviews and non-participant observation based guideline development task in the Vineland Adaptive Behavior Scale (VABS). The results showed that the ability of daily living skills more quickly controlled by the child on a personal subdomain drinking, wearing shoes, using utensils, dress according to the weather, the beginning of health care, and hair neatness. For domestic subdomain is using a tool, clean up and set the table. For subdomain communities are ordering food in a restaurant. For master developmental tasks in accordance with age VABS developmental tasks in the personal subdomain is eating, playing taps, wash hands, and put some clothes on. In domestic subdomain is cleaning house. To slow development tasks mastered by children in the personal subdomain undress, brush teeth, shower affairs, nasal hygiene, bathing without help, keeping the nails, and skilled health care. For domestic subdomains of moving something, use basic tools, using kitchen utensils, household cleaning tools, cleaning the house, repairing equipment and home appliances, cooking, and sewing clothes. For communities that subdomain safety in the home, the use of telephone or HP, safety on the road, meaning the money, right-left orientation, skills in the diner, calling time: day, date, year, calling time: hours and minutes, giving change, skilled use of the phone, spending money, planning spending, job skills, and manage money. The process of formation of daily living skills influenced by the acceptance of the parents, the ability of the children, the demands of the environment in which the child lives, the childs chronological age, the typical environment in which the task will be done, teaching and instruction loud and clear, and consistent in giving instruction.Keywords: autism, daily living skills.